Functionalization of activated carbon fiber through iron oxide impregnation for As(V) removal: equilibrium, kinetic, and thermodynamic analyses. Issue 23 (14th May 2016) - Lee, In; Park, Jeong-Ann; Kim, Jae-Hyun; Kang, Jin-Kyu; Lee, Chang-Gu; Kim, Song-Bae
Abstract: The aim of this study was to investigate the removal of As(V) from aqueous solutions using functionalized activated carbon fiber (ACF) as an adsorbent. The functionalized ACF was prepared through the impregnation of iron oxides on the surfaces of ACF. The X-ray fluorescence spectrometer analysis showed that carbon (C, 70.1%) and iron (Fe, 28.5%) were the major constituents of functionalized ACF. The N2 adsorption–desorption analysis showed that the Brunauer–Emmett–Teller surface area of functionalized ACF was determined to be 418.2 m 2 /g, which was 2.7 times smaller than that of raw ACF (1, 123.0 m 2 /g) due to the impregnation of iron oxide. From the batch experiments, the maximum adsorption capacity of As(V) in functionalized ACF was determined to be 1.208 mg/g. The adsorption of As(V) to functionalized ACF was sensitive to solution pH changes, decreasing from 0.045 to 0.029 mg/g with increasing pH from 2.6 to 8.9. Kinetic model analysis showed that the pseudo-second-order model was most suitable at describing the kinetic data. Equilibrium isotherm model analysis illustrated that the Redlich–Peterson model fitted well with the equilibrium data. Thermodynamic tests demonstrated that As(V) sorption to functionalized ACF increased with increasing temperature from 20 to 40°C, indicating the endothermic and spontaneous nature of sorption process (Δ H° = 38.02 kJ/mol, Δ S° = 149.15 J/K/mol, and Δ G° = –5.70 and –8.69 kJ/mol). This study demonstrated that the removal of As(V) by ACF could be enhanced via iron oxide impregnation.